Handbook of Research Methods in Public Administration, 2nd edition - Brandler, Sondra (CRC Press, 2020)
Describing new techniques and novel applications, Handbook of Research Methods in Public Administration, Second Edition demonstrates the use of tools designed to meet the increased complexity of problems in government and non-profit organizations with ever-more rigorous and systematic research.